Pedagogical methods, techniques, and approaches to enhance english speaking skills in third year bachillerato at unidad educativa fiscal República de Francia during the school year 2015-2016 - Valdiviezo Soto, Katty Stefany (2015)
All across the world, learning language diversity is fundamental to history, finances, job application, travelling, etc., but most importantly in education. Recently, learning English language is a requirement but it is not only improved communication, also the way of promoting worldwide understanding and culture exchange. This research project examined the implementation of the influence of methods, techniques, and approaches to enhance English speaking skills on third year bachillerato students at Unidad Educativa Fiscal “República de Francia” during the school year 2015 -2016 and aid teachers to develop speaking skills strategies more effectively…..